2016
DOI: 10.1099/jgv.0.000433
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel type of rotavirus species A in sugar gliders (Petaurus breviceps)

Abstract: To estimate the risk of interspecies transmission of rotavirus species A (RVA) from exotic pets to other mammalian species, the prevalence of RVA in sugar gliders (Petaurus breviceps) was investigated. RVAs were detected in 10 of 44 sugar gliders by reverse transcription (RT)-seminested PCR. These viruses were classified as G27P [3] and G27P[36] genotypes, with G27 and P[36] being new genotypes as assigned by the Rotavirus Classification Working Group. To characterize sugar glider RVA in detail, one strain, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…P [28] is the only genotype characterised in this study in the RVA P[I] genogroup that infects humans exclusively. Glycan array analyses showed that the P [28] VP8* recognised the H type 1 HBGA precursors (Figure 2), a property very similar to that of the P [6] and P [19] human strains in RVA P[II] genogroup, explaining why P [28] also causes sporadic cases in humans similar to that of P [19] and P [6] [14].…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…P [28] is the only genotype characterised in this study in the RVA P[I] genogroup that infects humans exclusively. Glycan array analyses showed that the P [28] VP8* recognised the H type 1 HBGA precursors (Figure 2), a property very similar to that of the P [6] and P [19] human strains in RVA P[II] genogroup, explaining why P [28] also causes sporadic cases in humans similar to that of P [19] and P [6] [14].…”
Section: Resultsmentioning
confidence: 81%
“…The [3], and P [7] that are known as sialic aciddependent RVs, infecting monkeys, dogs, bovine, porcine, horses and occasionally humans, as well as sialic acid-independent RVs that infect a wide ranges of animal species, including bovine, porcine, equine, monkey, lamps, murine, rabbits and humans. P[36] infects sugar glider [19], while P[37] infects pheasant [17,18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations